2019
DOI: 10.22616/j.balticsurveying.2019.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the Number of GCPS on the Accuracy of Photogrammetric Mapping from UAV Imagery

Abstract: (UAVs) very large datasets can be collected rapidly, covering significant surfaces with centimetre-scale resolution, with the consequence possibility to analyse geological structures of coastal areas within those datasets digitally. The monitoring of erosion mechanisms in fact requires high standards of precision to appreciate their effects. With the availability of a regular coastal monitoring programme being carried out in a large territory, UAVs can replace many of the conventional flights, with considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There are numerous studies in which it has been corroborated that increasing the number of GCPs improves the accuracy of results of UAV photogrammetric projects. For example, [59] needed approximately six to seven GCPs to obtain accuracy of about 15.6 cm, and specified that it was necessary to increase the number of GCPs to reduce error. In [60], a study was conducted to analyze the optimal number of GCPs for volumetric measurements in open pit mines; for accuracies of about 5.0 cm, they concluded that about 15 GCP/km 2 were needed.…”
Section: Image Processingmentioning
confidence: 99%
“…There are numerous studies in which it has been corroborated that increasing the number of GCPs improves the accuracy of results of UAV photogrammetric projects. For example, [59] needed approximately six to seven GCPs to obtain accuracy of about 15.6 cm, and specified that it was necessary to increase the number of GCPs to reduce error. In [60], a study was conducted to analyze the optimal number of GCPs for volumetric measurements in open pit mines; for accuracies of about 5.0 cm, they concluded that about 15 GCP/km 2 were needed.…”
Section: Image Processingmentioning
confidence: 99%
“…Characteristics of the repeated UAV campaigns are presented in Table 1. The photogrammetric processing of the UAV data was performed into Agisoft PhotoScan software, while Global Navigation Satellite System (GNSS) measurements were performed onshore utilizing a Leica GS08 GNSS receiver using square checkers in different colors placed throughout the research area and used for the georeferencing of the UAV images [17]. The high-quality option was selected for the alignment of the images, while the processing of the imagery was made using the original image size.…”
Section: Methodsmentioning
confidence: 99%
“…Global shutters still have the dominance over cheaper rolling shutter solutions. Publications of [24][25][26] describe the impact of GCP measurement accuracy and arrangement on image quality.…”
mentioning
confidence: 99%